2019
DOI: 10.1016/j.eap.2019.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to climate change in Afghanistan: Evidence on the impact of external interventions

Abstract: Climate change is a significant obstacle for farmers in the least developed countries like Afghanistan and adaptation support is exceptionally scarce. This paper provides evidence on the impact of the agriculture-related external support on farmers' adaptation to climate change in the Central Highlands of Afghanistan. To this end, we collected primary data from 1434 farmers whom we interviewed across 14 districts in Bamiyan, Ghazni, and Diakundi provinces. We employ quasi-experimental econometric methods, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…However, by randomly selecting women in one hospital in Central Afghanistan over an extended period of time, we sought to collect data from women whose characteristics are representative of this area. Comparing our sample characteristics with those of other study populations in the study area and in Afghanistan, we found them to be very similar (42,43). Thus, our sample is a good representative of women in this remote area and that our data is the best available and generalizable for Ghazni province or even the Hazarajat.…”
Section: Discussionsupporting
confidence: 67%
“…However, by randomly selecting women in one hospital in Central Afghanistan over an extended period of time, we sought to collect data from women whose characteristics are representative of this area. Comparing our sample characteristics with those of other study populations in the study area and in Afghanistan, we found them to be very similar (42,43). Thus, our sample is a good representative of women in this remote area and that our data is the best available and generalizable for Ghazni province or even the Hazarajat.…”
Section: Discussionsupporting
confidence: 67%
“…Major agricultural adaptations exercised by smallholder farmers include adjustments in farm operations timing, on-farm diversification, and soil-water management through improved irrigation, reduced tillage, contour farming, etc. (Below et al, 2012;Harmer & Rahman, 2014;Jawid and Khadjavi, 2019). It is uncertain how effective these plans and strategies are and will be in the future as little attention has been given on the monitoring and evaluation of smallholder farmers' adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…We use Nepal as a case study country. Smallholder farmers in poor economies like Nepal are comparatively more impacted by changing climatic parameters (Bandara & Cai, 2014;Morton, 2007;Dissanayake et al, 2019;Jawid and Khadjavi, 2019). In Nepal, agriculture contributes approximately one-third to the gross domestic product and employs about 70% of the country's population (MoF, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The data for this study were collected utilizing three methods viz: a pilot study, a focus group discussion, and a household survey. The pilot 1 Jawid and Khadjavi (2019) show that one of the adaptation measures employed by farmers in Afghanistan due to climate change is the use of improved seed varieties.…”
Section: Study Area and Data Collectionmentioning
confidence: 99%